2004
DOI: 10.5432/ijshs.2.111
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone Response to Training Regimen with Combined High-and Low-Intensity Resistance Exercises

Abstract: We had previously shown that performing a single set of resistance exercise at 50% of 1 repetition maximum (RM) added after a high-intensity, low-repetition exercise (strength-type regimen) greatly enhanced growth hormone (GH) secretion [Goto et al. (2003)]. The present study aimed to investigate the effect of an additional set at 50% to 20% of 1RM after a strength-type regimen on anabolic hormone secretion. Eight male subjects performed bilateral knee extension exercises using a strength-type regimen (5 sets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…In a series of studies, the group of Takamatsu and colleagues investigated the effects of adding fatiguing low‐to‐moderate intensity sets after high‐intensity sets on adaptations in muscle strength and size as well as on acute hormonal responses (Choi et al, 1998; Masuda et al, 1999; Goto et al, 2003a, b, 2004). Choi et al (1998) demonstrated a high rate of increase in quadriceps muscle area after a regime where high‐intensity sets (70–80% of 1RM) were followed by sets to fatigue at succeedingly lower loads (50–60% and 40–50% of 1RM), with 30 s rest periods between the decrements in loads.…”
Section: Practical and Health Aspectsmentioning
confidence: 99%
“…In a series of studies, the group of Takamatsu and colleagues investigated the effects of adding fatiguing low‐to‐moderate intensity sets after high‐intensity sets on adaptations in muscle strength and size as well as on acute hormonal responses (Choi et al, 1998; Masuda et al, 1999; Goto et al, 2003a, b, 2004). Choi et al (1998) demonstrated a high rate of increase in quadriceps muscle area after a regime where high‐intensity sets (70–80% of 1RM) were followed by sets to fatigue at succeedingly lower loads (50–60% and 40–50% of 1RM), with 30 s rest periods between the decrements in loads.…”
Section: Practical and Health Aspectsmentioning
confidence: 99%
“…Resistance exercise for developing maximal voluntary strength and muscle hypertrophy, which consists of five repetitions at 90% of one repetition maximum (1RM), as well as a resistance exercise to repetition failure at 30% or 50% of 1RM per set, produces more blood lactate and growth hormones than that for developing maximal voluntary strength alone [24]. They also demonstrated that the resistance exercise with only five repetitions × 90% of 1RM produced less growth hormones [24]. Growth hormone has been clearly shown to stimulate protein synthesis and to facilitate muscle hypertrophy [25].…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have quantified the metabolic stress incurred during sessions of drop-set RT. For example, Goto et al 104 demonstrated that the addition of one drop with 20, 30, or 50% of 1-RM after finishing a standard session of RT (5 sets, 90% of 1-RM) significantly increased GH and blood lactate. Years later, the same research team concluded that drop-set training stimulated significant decreases in muscle oxygenation, especially in trained lifters who have greater muscle thickness than their untrained counterparts 105 .…”
Section: Applications Of Rt With High-tutmentioning
confidence: 99%
“…In a longitudinal design, Goto et al 107 concluded that strength training (5 sets, 90% of 1-RM) and strength training with the addition of one drop set (25–35 repetitions with 40–50% of 1-RM) both led to significant increases in endurance, strength, and rate of force development. However, the drop-set group had significantly greater increases in 1-RM for leg press, maximal isokinetic strength at a fast velocity (e.g., 300 degrees/second), and muscular endurance, which was quantified as total work performed (load x repetitions) during one set of knee-extension to failure with 30% of maximal voluntary contraction 107 . Because total training volume was not matched, it is difficult to conclude if the differences between groups occurred strictly because of the metabolic stress imposed by the drop-set condition.…”
Section: Applications Of Rt With High-tutmentioning
confidence: 99%